Empowering Woman’s Farmer Group (KWT) Mekar-Sari Kintamani in postharvest handling of Siamese oranges with the application of nanocoating-konjac - Luh Suriati; I K Selamet; N K Mardewi; A A S Manik Cindrawati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The rising demand for Siam Kintamani oranges is driven by heightened public health awareness. Its bioactive components benefit human health, but their quality is swiftly deteriorating. Oranges must be preserved using the Nanocoating-konjac application procedure. Nanocoating-konjac is an immersion-applied natural preservative solution derived from konjac. Efforts to develop the autonomy and welfare of a community are made through village community empowerment. The Woman’s Farmer Group (KWT) Mekar-Sari (partners) is a group of women cultivators in the village of Pengejaran, Kintamani District, Bali Province, Indonesia, who require assistance to increase the shelf life of Siamese oranges. Using Nanocoating-konjac as a natural preservative for Siamese oranges can support community service objectives, such as enhancing (both soft and hard) skills and forming/developing economically and socially independent communities. By engaging in community service, partners gain the knowledge and abilities to manage natural resources and an entrepreneurial spirit, expanding their business and marketing opportunities. Community service activities are conducted through training using lecture methods, discussions, demonstrations, queries and answers, while an evaluation is carried out after handling the program. Seventy percent of the twenty group members who participated in community service had never preserved Siamese oranges, while thirty percent had done so. After participating in these activities, all members understand the materials and procedures, and they continue to apply nanocoating to citrus fruits based on what is marketed. Coating citrus fruits with nano-konjac adds value and becomes a community income source.